Mathematics for Sustainable Development (MATH4SDG): A Capacity Building Project in Uganda and Tanzania - Dahl, Bettina; Alendal, Guttorm; Mureithi, Eunice; Mango, John (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Mathematics for Sustainable Development, MATH4SDG, is a capacity building project funded by the NORHED II programme under the Norwegian Agency for Development Cooperation (NORAD) involving the mathematics departments at the University of Dar es Salaam (Tanzania), Makerere University (Uganda), and the University of Bergen (Norway). The project aims to enhance mathematics education and research in Tanzania and Uganda. Central to MATH4SDG is 11 PhD-students, with four in secondary mathematics education and seven in applied mathematics and statistics. All PhD-students are supervised by both Norwegian and local supervisors. Another component involves outreach to schools and research collaboration workshops with local industry and governmental organizations. By aligning university mathematics programmes with the needs of these stakeholders, graduates become more attractive to employers and the workforce benefits from a strong foundation in mathematics and its applications thus aiding in the digital transformation for sustainable development. MATH4SDG contribute to educating much needed schoolteachers and enhance the proficiency in mathematics.